”A Debt on your Heart”: Exploring the impact of student precarity on Education Studies students at a UK university - Andrew Edgar; Ben Johnson; Stephen Dixon (Educational Futures, 2024)
Drawing on Guy Standing’s theory of ‘precarity’ (2021), this article addresses a gap in the research around the experience of student precarity on UK Education Studies courses and how this precarity impacts their perceptions of the education system they aim to enter as professionals. Using an interpretivist methodology, 19 students from the lowest quintile on the Index of Multiple Deprivation (Gov, 2019) took part in four focus groups in which they were asked open-ended questions about their experience of university in the cost-of-living crisis and life post-covid, and how they balance home, life, studies and work commitments. These were around areas such as their understanding of precarity and its impact on their studies and their perception of their place in the wider education system. Using thematic analysis, the main findings were: a feeling of foreboding towards the future; struggling to manage work and studies under the pressure caused by future debt and a resigned acceptance of precarity once entering the education workforce. Students felt a sense of vulnerability about the future resulting in heightened anxiety; furthermore, the ability to study without financial worries is denied to these non-traditional students leading to them having to take on more work which compromised time available for study. Finally, students felt disempowered to change the wider education system they aim to enter as professionals.